Dramaturgi Personal Branding Andika-Hendrar dalam Membangun Citra Politik Melalui Instagram (Studi Kasus Kontestasi Calon Pilgub Jateng 2024) - Idelia, Rachel Tivara; Putranto, Algooth (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This Study analyzes the strategic dramaturgy implemented by the 2024 Central Java Governor candidate pair, Andika Perkasa and Hendrar Prihadi, in building their political image via Instagram. The dramaturgical approach highlights how candidate pairs create a "political stage" through symbols, narratives and structured public interactions to attract voters' attention. This research uses a qualitative descriptive method with data analysis and social media content analysis. The research results show that dramaturgical strategies play an important role in building public perceptions of the couple as firm, popular and inclusive leaders. This article also presents a tabular analysis of the dramaturgical elements used by Andika and Hendrar in various campaign contexts.